2017
DOI: 10.1080/00220671.2017.1310711
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dyad reading and text difficulty on third-graders’ reading achievement

Abstract: This study replicated, with modifications, previous research of dyad reading using texts at various levels of difficulty (Morgan, 1997). The current project measured the effects of using above-grade-level texts on reading achievement and sought to determine the influences of dyad reading on both lead and assisted readers. Results indicate that weaker readers, using texts at two, three, and four grade levels above their instructional levels with the assistance of lead readers, outscored both proficient and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…In the research on peer collaboration carried out by Morgan et al (2000), they also found that when texts were two grade levels above the readers' abilities, reading scores in standardised tests improved more than when texts were much higher or at the readers' level. More recent research has also found that the assisted readers reading texts two grade levels above their instructional levels showed the most robust gains in oral reading fluency and comprehension (Brown et al 2018). These research findings are also reinforced by the wider research comparing collaborative and individual learning which has found that learning efficiency is greater in group learning than individual learning when the problem-solving tasks are relatively complex (e.g., Kirschner et al 2009;Laughlin et al 2002;Laughlin et al 2006).…”
Section: Reading Comprehension and Text Complexitymentioning
confidence: 90%
“…In the research on peer collaboration carried out by Morgan et al (2000), they also found that when texts were two grade levels above the readers' abilities, reading scores in standardised tests improved more than when texts were much higher or at the readers' level. More recent research has also found that the assisted readers reading texts two grade levels above their instructional levels showed the most robust gains in oral reading fluency and comprehension (Brown et al 2018). These research findings are also reinforced by the wider research comparing collaborative and individual learning which has found that learning efficiency is greater in group learning than individual learning when the problem-solving tasks are relatively complex (e.g., Kirschner et al 2009;Laughlin et al 2002;Laughlin et al 2006).…”
Section: Reading Comprehension and Text Complexitymentioning
confidence: 90%
“…We have a few readings about this that we’ll focus on over the next couple of days. We’ll use our regular partner reading strategy [also known as dyad reading; Brown, Mohr, Wilcox, & Barrett, ].The guidelines were posted on the wall (see Figure ) and students were paired up, with a stronger and weaker reader working together. They immediately got to work, reading the assigned text for the day and talking about rocks and fossils.…”
Section: The Will Of Comprehensionmentioning
confidence: 99%
“…We have a few readings about this that we’ll focus on over the next couple of days. We’ll use our regular partner reading strategy [also known as dyad reading; Brown, Mohr, Wilcox, & Barrett, ].…”
Section: The Will Of Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that students can successfully comprehend difficult texts. For example, two studies compared young readers partner reading with texts at different difficulty levels and found that the greatest gains occurred for students who read texts two years above their current level (Brown, Mohr, Wilcox, & Barrett, 2017;Morgan, Wilcox, & Eldredge, 2000). Although some studies find no difference in terms of comprehension outcomes when students read different levels of texts (Mathes & Fuchs, 1993;O'Connor, Swanson, & Geraghty, 2010), others have shown that students grow in fluency and comprehension when teachers use difficult texts in conjunction with strong instructional support (Stahl & Heubach, 2005).…”
Section: Value Of Difficult Textsmentioning
confidence: 99%